Reconstructing the professional identity of compulsory secondary education teachers in curricular sustainability - María Rosario Mendoza Carretero; Belén Sáenz Rico de Santiago (Revista Española de Pedagogía)
The current situation with its constant uncertainty regarding the new social and planetary challenges that societies face demands commitment and active participation by members of the public to achieve economic, social, and environmental transformations that favour a more sustainable planet. Establishing an alignment with sustainability in all its dimensions in secondary school curricula is necessary so that people can lead social changes in line with the sustainable development goals of the 2030 Agenda. This research seeks to establish whether the specialisation profile of compulsory secondary education teachers at national level interferes with the incorporation of the sustainability approach in the classroom. The sample comprised n = 208 participants identified through non-probabilistic sampling using the snowball technique. The results of a descriptive and inferential analysis showed that the participating teachers try to respond to the challenges of the 21st century (such as social inequalities, pollution and degradation of ecosystems, depletion and destruction of vital resources, etc.), but do not approach them from the necessary interdisciplinary and complex perspective, instead largely covering the environmental dimension. This makes it difficult for secondary school students to address global challenges holistically and explore ways of transformation from an approach centred on sustainability. It is therefore necessary for lifelong learning to aid teachers in the reconstruction of their teaching work, overcoming the current outlook, which is fragmented by disciplines or specialisations, in order to promote an interdisciplinary approach through cooperation and collaboration. In this way, true eco-social literacy would be consolidated in order to meet the new demands of the education system in terms of sustainability.